Big Genes, Small Effectors: Pea Aphid Cassette Effector Families Composed From Miniature Exons - Dommel, Matthew; Oh, Jonghee; Huguet-Tapia, Jose Carlos; Guy, Endrick; Boulain, Hélène; Sugio, Akiko; Murugan, Marimuthu; Legeai, Fabrice; Heck, Michelle; Smith, C. Michael; White, Frank F. (Frontiers in Plant Science, 2020)
Aphids secrete proteins from their style that evidence indicates function similar to pathogen effectors for virulence. Here, we describe two small candidate effector gene families of the pea aphid, Acyrthosiphon pisum, that share highly conserved secretory signal peptide coding regions and divergent non-secretory coding sequences derived from miniature exons. The KQY candidate effector family contains eleven members with additional isoforms, generated by alternate splicing. Pairwise comparisons indicate possible four unique KQY families based on coding regions without the secretory signal region. KQY1a, a representative of the family, is encoded by a 968 bp mRNA and a gene that spans 45.7 kbp of the genome. The locus consists of thirty-seven exons, thirty-three of which are 15 bp or smaller. Additional KQY members, as well as members of the six member KHI family, share similar features. Differential expression analyses indicate that the genes are expressed preferentially in salivary glands. Proteomic analysis on salivary glands and saliva revealed eleven KQY members in salivary proteins, and KQY1a was detected in an artificial diet solution after aphid feeding. A single KQY locus and two KHI loci were identified in Myzus persicae, the peach aphid. Of the genes that can be anchored to chromosomes, loci are mostly scattered throughout the genome, except a two-gene region (KQY4/KQY6). We propose that the KQY family expanded in A. pisum through combinatorial assemblies of a common secretory signal cassette and novel coding regions, followed by classical gene duplication and divergence.